Hemorrhoid Degrees of Pregnant Women in the Use of Suppository Phaleria macrocarpa - Astuti, Siti Choirul Dwi; Mohamad, Selvi; Nurlaily Z, Sri; Damiti, Sukmawati A.; Mashar, Harlyanti Muthmai’nnah (JURNAL INFO KESEHATAN, 2024)
Increased progesterone levels during pregnancy can lead to haemorrhoids, which require proper management to minimize risks to both the mother and fetus. Since haemorrhoidectomy is not a suitable option for pregnant women, alternative treatments with minimal side effects are needed. This study aimed to evaluate the effectiveness of Phaleria macrocarpa suppositories in reducing the degree of haemorrhoids in pregnant women. This study employed a true experimental design with a cross-sectional approach. The study population consisted of pregnant women selected through purposive sampling. Data were collected using observation sheets and analyzed using the Wilcoxon test. The results study show that among pregnant women who used standard suppositories, 23 participants (71.8%) showed no change in the degree of haemorrhoids, while 9 participants (28.8%) experienced a reduction in severity. In contrast, all 32 participants (100%) who used Phaleria macrocarpa suppositories experienced a decrease in haemorrhoid severity. Statistical analysis showed a significant difference (p < 0.05) between the two groups, with a p-value of 0.0013, indicating that Phaleria macrocarpa suppositories were significantly more effective in reducing haemorrhoids compared to standard suppositories. The conclusion is Phaleria macrocarpa suppositories effectively reduce the severity of haemorrhoids in pregnant women and may serve as a safer alternative to conventional treatments. Further research with larger sample sizes and long-term follow-ups is recommended to validate these findings and explore the potential mechanisms of Phaleria macrocarpa in haemorrhoid treatment.